2018
DOI: 10.1017/s1047951117002967
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of aortic coarctation after conventional balloon angioplasty in neonates

Abstract: In centres in which the neonatal ICU is inexperienced, balloon angioplasty is particularly recommended. In developing neonatal clinics, balloon angioplasty, when performed on patients at their earliest possible age, delays actual corrective operation to a later date, which in turn provides less risky surgical outcomes in infants who are gaining weight, growing, and do not have any haemodynamic complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The currently main surgical strategies (7)(8)(9) for CoA associated with intracardiac anomalies in infants include the following: (1) surgical repair of CoA and pulmonary banding (if necessary) at the first stage, followed by subsequent repair of intracardiac defects; (2) single-stage repair of CoA and intracardiac defects with the use of selective brain perfusion or DHCA; and (3) single-stage repair with double incisions including lateral thoracotomy for CoA and median sternotomy for intracardiac defects. In the 1990s, several studies reported primary repair for CoA and second-stage repair for VSD (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…The currently main surgical strategies (7)(8)(9) for CoA associated with intracardiac anomalies in infants include the following: (1) surgical repair of CoA and pulmonary banding (if necessary) at the first stage, followed by subsequent repair of intracardiac defects; (2) single-stage repair of CoA and intracardiac defects with the use of selective brain perfusion or DHCA; and (3) single-stage repair with double incisions including lateral thoracotomy for CoA and median sternotomy for intracardiac defects. In the 1990s, several studies reported primary repair for CoA and second-stage repair for VSD (10,11).…”
Section: Discussionmentioning
confidence: 99%